Construction of a High-Resolution Mobile γ-Camera System for Mammography Study - Zioga, M.; Kontos, M.; Maintas, D.; Mikeli, M.; Rapsomanikis, A.-N.; Stiliaris, E. (HNPS Advances in Nuclear Physics, 2019)
A small-field portable γ-Camera system based on a Position Sensitive Photomultiplier Tube (PSPMT) has been recently developed in our Lab. This γ-Camera system has been characterized on planar and tomographic level and exhibits high efficiency and resolution (0.95 ± 0.5 mm spatial resolution on planar imaging and 0.20μCi sensitivity on a tomographic level). Even though a portable γ-Camera system has many advantages, it shows a strong dependence from the operators hand stability which greatly affects the quality of the acquired image. To overcome these circumstances a need for a motion correction technique arises. In the present work, a simple a low cost solution to overcome this stability problem by means of commercially available equipment is proposed. It is based on the Nintendo’s Wii Remote sensors, a small handheld device which can be easily coupled to the portable camera. It comprises both, a 3D-accelerometer which reports the three detected components of the gravity acceleration and an infrared sensor for a fix-point distance evaluation. The Wii Remote sensors device is wireless and operates with modern communication protocols (Bluetooth). Based on the received accelerometer and infrared-sensor data by a DAQ system developed on the LabVIEW environment, the γ-Cameras DAQ system is capable to store all the primary parameters on an event-by-event basis and to perform the necessary motion correction in real time. Some typical image correction results are presented in the current work.